Furanocoumarin compounds isolated from Dorstenia foetida potentiate irinotecan anticancer activity against colorectal cancer cells - Pengnam Supusson; Jitkaroon Watcharapa; Srisuphan Roongtiwa; Wongprayoon Pawaris; Rayanil Kanok-On; Charoensuksai Purin (Acta Pharmaceutica)
Although the anticancer activity of Dorstenia foetida was already observed, the chemical entity responsible for this activity remained unidentified. In this study, the cytotoxic activity of two furanocoumarin compounds, i.e., 5-methoxy--3-(3-methyl-2,3-dihydroxybutyl)-psoralen (1) and 5-methoxy-3-(3-methyl-2,3-dihydroxybutyl)-psoralen diacetate (2) isolated from ethyl acetate fraction of D. foetida (whole plant) was investigated in several cancer cell lines including HN22, MDA-MB-231, HCT116, and HT29. The results revealed that compound 2 exhibited cytotoxic activity, particularly against colorectal cancer cell lines HCT116 and HT29. The interplay between compound 2 and irinotecan (Iri) showed synergism against HCT116, which was analyzed by CompuSyn software. The simulation revealed that, at the molar ratio of Iri:2 of 1:40, the concentration predicted to achieve a 90 % inhibitory effect when used in the combination would be ~28- and ~4-fold lower than the concentration of compound 2 and Iri, resp., when used individually. Finally, the percentage of apoptotic cells in the HCT116 line treated with the combination was markedly higher than in the cells treated with the individual agent (60 % apoptotic cells for the combination compared to 17 and 45 % for Iri and compound 2 monotherapy, resp). In conclusion, our results identified compound 2 as a plant-derived compound exhibiting anticancer properties that can act synergistically with Iri and warranted further research to assess the potential of this synergism for colorectal cancer treatment.